MANAGEMENT OF MENTAL DISORDER PATIENTS (ADHIATMIKA DHUKA) IN BALI PROVINCE HOSPITALITY - Sumantra, I Nengah (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2021)
This research is focused on the discussion of (1) integration between traditional and conventional medicine in the RSJ (Mental Hospital) of Bali, (2) the form of a combination of traditional medicine with conventional medicine for mental disorder patients at Mental Hospital of Bali, (3) the impact of integrating traditional medicine and conventional in mental patients at Mental Hospital of Bali. The theory used in analyzing the three problem formulations in this study, namely: (1) psychoanalytic theory, (2) ethnomedicine theory, and (3) perception theory. This research uses the method of documentation, literature study, observation and interviews. The results of this study indicate the following points. First, the factors that cause psychiatric rehabilitation patients at RSJ Bali integrate traditional and conventional medicine consisting of internal factors, e.g., beliefs, needs for holistic nursing care, religion, social, and culture, and also external factors, e.g., state legitimacy towards traditional medicine and western biomedical weakness. Second, the form of traditional medicine for mental illness patients at RSJ Bali Province consists of traditional forms, e.g., diagnosis (nengerin), peruwatan (bhuta Yajna) and spells, speech, dharma wacana (spiritual ceremony), prayer, and text-based handling (manuscripts) of medicine and a combination of traditional and modern techniques, and also conventional forms of treatment for psychoanalysis, cognitive behavioral approaches (cognitive behavior), humanistic approaches, and other types of therapy. The form of combining traditional and modern techniques consists of diagnosis, improvement of mental development, the use of drugs, and treatment by spiritual means. Third, traditional and conventional treatments for mental patients at RSJ Bali have an individual impact, social impact, psychological impact on patients, the impact of power, and the impact of community culture.